(untitled) (Research, Society and Development, 2020)
This paper aimed to characterize the sociodemographic and professional profile of firefighters in the metropolitan region of Belem. The pape is Cross-sectional, quantitative, descriptional study. results found that 92.23% of the military personnel are male and 7.77% female. Regarding the level of the officers, 76.61% of male personnel are married or in a common-law marriage, in the rank of Major represents 26.61% while 49.19% of the officers have over 20 years of service. Women married or in a common-law marriage represents 45.45% while single union represents 45.45%, the rank of Lieutenant-Colonel predominates with 31.82%, while 36.37% have between 11 to 15 years of service. In both genders, College degree and age group ratings from 40 to 49 years old are predominant. Among the enlisted personnel prevail male gender, married or common-law marriage, with 72.68%, 48.29% of male enlisted personnel have graduated from high school, 35.08% represents age group of 40 to 49 years old, undergraduate education is predominant among this group. Sergeants represent 35.38%, and the time of service, with over 20 years, represents 46.88%. The female gender personnel is 50.00% single, 48.61% have a college degree, the age group of 30 to 39 years, represents 61.11%, the corporal rank prevails, with 51.39%, and length of service from 11 to 15 years, represents 51.39%. This study concludes that the percentage of women in the force still displays low ratings stressing that 529 military personnel have more than 20 years of service, and will soon retire and leave the institution.